Day-End Effect: Ketidakkonsistensian HargaPenutupan Akhir Hari Perdagangan dalam Perepresentasian Nilai Saham (Studi Empiris Berbasis Intraday Data, Bursa Efek Indonesia 2006) - S u m i y a n a S u m i y a n a (The Indonesian Journal of Accounting Research, 2013)
This research investigates day-end effect over every 30 minutes interval of the day. Especially, this research investigates that closing prices in the every latest of a day are not consistently represent stock values. Having identified the existence of day-end effect, this research continued to investigate the latest 30 minutes interval return in every day in comparison with periodical returns in others 30 minutes interval return. This study uses regression analysis with multiple dummies constructed by separating trading periods in every day into 12 return periods. Samples of the data are the firms listed in LQ 45 indexes for the year of 2006. This research results that the latest 30 minutes interval return in every day increased dominantly, or the hypothesis "reversed 'J' curve" was evidenced validly. Using size, trading volume and bid ask spreads as controling variables, this research also suggests that the latest 30 minutes return in every day which always increased dominantly are found correct and valid. Finally, this research inference that day-end effect is due to the increase in the frequency of asks prices and the magnitude of trading volume at the day-end. Furthermore, this research concludes that imperfect substitutes and price-pressure hypotheses which contradict the efficient market hypothesis are supported.